STRATEGI PROMOSI DALAM MENJARING CALON MAHASISWA BARU PADA UPBJJ-UT PALU DI WILAYAH PROPINSI SULAWESI TENGAH - Yuyun Yunita Puspa; Andi Alimuddin Unde; Tuti Bahfiarti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2014)
Abstract Open University (UT) is a university that implement distance learning system, has three main components that affect the quality of learning, the third component includes teaching materials, student service components and component testing, of three components determines the learning process in distance education system. This research aimed (1) to determine the promotional strategy which had been carried out by Palu Distance Learning Program Unit of the Open University (UPBJJ-UT Palu) in recruiting new students in order to increase the number of student; (2) to analyze the obstacles faced by the UPBJJ-UT Palu in implementing their promotional strategies. The study was a descriptive-qualitative research with the focus on the overall description-qualitative research with the focus on the overall description of the form, function, and meaning of the ban expressions. The research results revealed that the implementation of the promotional strategies in recruiting the new students, the UPBJJ-UT Palu 4 (four, the UPBJJ-UT Palu 4 (four) mixture promotions:the Personal Selling, Publicity by the Public Relation, Advertisement, and Sponsorship. The promotional strategies which the UPBJJ-UT Palu had used were sticking to the ran, setting the targets, designing messages, excecuting promotions, and evaluating the results. However, the results of the promotions were not yet optimum because of the annually fluctuation of the number of students. Meanwhile, the obstacles faced during the implementation of the promotions were the long distance accesses or the inaccessible geographical locations, the shortages of the human resources especially the inability of the human resources to communicate, the non-maximum monitoring and evaluation of the Sosprom, the lack of funds to pay for the Sosprom activities, and the inadequate time given to the Sospromactivities considering the conditions of the geographical locations which were difficult to reach. AbstrakUniversitas Terbuka (UT) merupakan universitas yang menerapkan sistem belajar jarak jauh yang memiliki tiga komponen utama yang mempengaruhi kualitas pembelajaran, ketiga komponen tersebut meliputi bahan ajar, komponen pelayanan mahasiswa dan komponen pengujian, ketiga komponen ini menentukan proses belajar dalam system pendidikan jarak jauh. Penelitian ini bertujuan untuk mengetahui strategi promosi yang telah dilakukan oleh Unit Program Belajar Jarak Jauh Universitas Terbuka Palu (UPBJJ-UT Palu) dalam menjaring mahasiswa baru guna meningkatkan jumlah mahasiswa; dan menganalisis kendala yang dihadapi oleh UPBJJ-UT, Palu dalam menjalankan strategi promosi. Penelitian ini mengunakan metode pengumpulan data yang digunanakan adalah observasi, wawancara, dan studi dokumen. Data dianalisis secara deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa, strategi promosi menjaring mahasiswa baru di UPBJJ-UT Palu menggunakan empat bauran promosi yaitu, Personal Selling, Humas/Publisitas, iklan dan sponsorship. Strategi promosi yang dilakukan UPBJJ-UT Palu sudah mengikuti ran, menentukan tujuan, merancang pesan, melaksanakan promosi hingga evaluasi hasil. Namun, hasil promosi tersebut belum optimal karena masih terjadi fluktuasi jumlah mahasiswa setiap tahun. Sementara hambatan- hambatan yang ditemukan pada waktu pelaksanaan kegiatan promosi, yakni letak geografis yang sulit dijangkau; keterbatasan sumber daya manusia yang memiliki kemampuan komunikasi; monitoring dan evaluasi mengenai Sosprom yang masih kurang maksimal; kurangnya anggaran dan waktu yang diberikan untuk kegiatan Sosprom mengingat kondisi geografis yang sulit dijangkau.